Contribution of Aldehydes and Their Derivatives to Antimicrobial and Immunomodulatory Activities - Mariam Nasser Aljaafari; Maryam Abdulraheem Alkhoori; Mohammed Hag-Ali; Wan-Hee Cheng; Swee-Hua-Erin Lim; Jiun-Yan Loh; Kok-Song Lai (Molecules, 2022)
Essential oils (EOs) are intricate combinations of evaporative compounds produced by aromatic plants and extracted by distillation or expression. EOs are natural secondary metabolites derived from plants and have been found to be useful in food and nutraceutical manufacturing, perfumery and cosmetics; they have also been found to alleviate the phenomenon of antimicrobial resistance (AMR) in addition to functioning as antibacterial and antifungal agents, balancing menstrual cycles and being efficacious as an immune system booster. Several main aldehyde constituents can be found in different types of EOs, and thus, aldehydes and their derivatives will be the main focus of this study with regard to their antimicrobial, antioxidative, anti-inflammatory and immunomodulatory effects. This brief study also explores the activity of aldehydes and their derivatives against pathogenic bacteria for future use in the clinical setting.